Performance Impact Employee Competence - Almansyah Rundu Wonua (SEIKO : Journal of Management & Business, 2023)
This study's goal is to determine whether certain factors knowledge, training, competence, and motivation have a simultaneous or partial impact on the tourism and cultural workers in Garut Regency, West Java. The research design employs a quantitative descriptive research methodology. Thirty-one employees of the tourism and culture office in the Garut Regency participated in the survey. This study used a sample of 31 respondents from the entire workforce of the tourism and culture office in the garut regency. According to the study's conclusions, the effectiveness of the Office of Tourism and Culture in Garut Regency is significantly influenced by knowledge, training, competence, and motivation. Employee performance is expected to increase and improve as a result of the Office of Tourism and Culture in Garut Regency's personnel continuing to advance their current knowledge, training, competence, and motivation. Keywords: Performance, Competence, Motivation, Training, Knowledge.